EFFECT LOADING DC MOTOR ON CONVEYOR (Science and Technology (SciTech), 2022)
Abstract - In the industrial world, all working processes must be controlled by a system that can be controlled with the aim of increasing efficiency and minimizing the risk of errors. Likewise the production process with a controllable system, in this case the process of separating goods based on certain criteria as needed with PLC as a control base will make the combination of a complex and interrelated system to improve the performance of the system. Loading analysis of the prototype of the goods separator system based on the height based on this PLC, with a power supply voltage of 12 Volt DC to run the prototype system, it was found that the load that can be passed on each conveyor is a load ranging from 10-120 gr with the overall required current. 2.15 A, the required voltage is 12Vdc ± 8.99%, the time required by the system with a minimum time = 177ms and a maximum time = 285ms where the driver used is a 12 Volt DC motor eg-530ad-2f coupled with an elastic rubber van-belt 5mm. If it exceeds the recommended load above, then there are several conveyors that cannot move due to overload, namely on a tilted conveyor with an angle of 300, a transfer motor and a separator motor which makes the system performance less than optimal.